Analysis of digital marketing strategies on the development of UMKM in Bogor district case study: MSME Pearl Mat in Kemang District, Bogor Regency - Erny Indrayanti; Awang Darmawan Putra; Popy Novita P; Raden M Jiddan Aziz (Institute of Computer Science (IOCS), 2024)
This research discusses the marketing strategy and growth of Mutiara Keset MSMEs in Bogor Regency, with a focus on marketing techniques, business plan patterns, digital marketing, and the role of government. The method used is a qualitative approach with a case study method. Data was collected through in-depth interviews with the owners of Mutiara Keset MSMEs, direct observation of marketing and operational activities, as well as analysis of related documents, such as business plans and financial reports. Marketing techniques used include selecting products with different colors to increase attractiveness and influence consumer psychology, as well as a strong brand identity to build customer trust and loyalty. The Mutiara Keset MSME business plan pattern includes product diversification strategies, setting the right prices, choosing strategic marketing locations, and promotion through exhibitions and social media. Additionally, digital marketing involves the use of online and mobile platforms to increase visibility and interaction with customers. The government's role in supporting MSMEs is realized through policies, facilities and support for innovation and collaboration. The success of Mutiara Keset MSMEs in overcoming challenges and achieving stable growth is an example for other MSMEs in developing business